Assessment of reliability and validity of a nursing tool used to examine knowledge, attitude, and practices of professional nurses in writing nursing care plans at a teaching hospital in Gauteng Province, South Africa - Lodi, Louisa M.; Randa, Moreoagae B.; Ntuli, Samuel T.; Matlala, Sogo F. (Bentham Science Publisher, 2023)
Background: A nursing care plan is a guideline developed for a patient's needs. A well-documented care plan provides holistic patient-centred care and includes assessing, evaluating, and administering a variety of interventions as well as teaching patients and families. There are existing tools to measure nurses' knowledge, attitude, and practices in writing nursing care plans in many countries. However, cultural differences and most of the tools do not cover region-specific aspects of diseases, making it challenging to be used between countries. Objective: Thisstudy aimed to develop and validate a tool for determining the knowledge, attitudes, and practices of nurses in writing nursing care plans at a teaching hospital in Gauteng province, South Africa. Methods: A cross-sectional study was conducted among 218 registered nurses in selected hospital wards. Reliability was examined using Cronbach alpha and item-total correlation, while validity was assessed using Exploratory Factor Analysis (EFA EFA) and convergent validity. SPSS for Windows (version 10.0; SPSS, Inc., Chicago, IL, USA) was used to analyze data. Results Cronbach's alpha was 0.75 for knowledge, 0.74 for attitude, and 0.77 for practices. The item-total correlation values ranged from -0.203 to 0.742. Kaiser-Meyer-Olkin was 0.877, 0.793, and 0.797 for the three dimensions, respectively and the Bartlett test was significant (p< 0.0001). The EFA showed that all the items had loadings ≥0.5 except for item A1. Knowledge and practice had a good convergent validity. Implications for Nursing Efforts to develop, validate and implement a new instrument to assess nursing knowledge, attitudes, and practice in writing nursing care plans improve communication between nursing staff, and involve patients more in their care, resulting in fewer medical errors and improving the quality of patient care. Conclusion: This study indicates that the tool has satisfactory reliability, and the use of EFA for the investigation of validity is adequate, but one item in the attitude dimension has a lower threshold value. Further confirmatory factor analysis studies with a larger sample size are needed to support construct validity.
Journal article published in The Open Nursing Journal
Keywords: Exploratory factor analysis; Nursing care plan; Registered nurses; Validation; Questionnaire; Patient care; Nursing care plans; Nursing -- Effect of managed care on; Patient-centered health care; Nursing -- South Africa -- Gauteng